2017
DOI: 10.1097/rlu.0000000000001769
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Membrane Antigen–Targeted Imaging With [18F]DCFPyL in High-Grade Gliomas

Abstract: High-grade gliomas (World Health Organization grade III-IV) are highly lethal primary brain tumors. Imaging modalities, including MRI and FDG PET, provide a limited ability to differentiate treatment effects (such as radiation necrosis) from recurrent or residual tumor. As the first step in validating the applicability of prostate-specific membrane antigen (PSMA)-targeted imaging in high-grade gliomas, we evaluated the ability of the PSMA-targeted small molecule

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 7 publications
2
46
0
Order By: Relevance
“…Our data confirm the high intertumoral heterogeneity in gliomas and reveal tumor targets in subsets of gliomas that are associated with other cancer types, opening new avenues for targeted therapy. Our data confirm expression of the prostate cancer marker PSMA on microvasculature of glioblastoma, possibly providing opportunities for tumor-vascular targeting [55][56][57]. In a recent publication high expression levels of androgen receptor were described in glioblastomas, that actually translated into sensitivity to the AR antagonist enzalutamide [39].…”
Section: Discussionsupporting
confidence: 78%
“…Our data confirm the high intertumoral heterogeneity in gliomas and reveal tumor targets in subsets of gliomas that are associated with other cancer types, opening new avenues for targeted therapy. Our data confirm expression of the prostate cancer marker PSMA on microvasculature of glioblastoma, possibly providing opportunities for tumor-vascular targeting [55][56][57]. In a recent publication high expression levels of androgen receptor were described in glioblastomas, that actually translated into sensitivity to the AR antagonist enzalutamide [39].…”
Section: Discussionsupporting
confidence: 78%
“…There are ample studies utilizing PSMA-based imaging agents for tumor detection in prostate cancer (24)(25)(26)(27)(28)(29)(30)(31), high-grade gliomas (32)(33)(34)(35)(36) and lung BMs (33), as well as in follicular thyroid adenoma (37), metastatic renal cell carcinoma (38) and in melanoma and small cell lung cancer (SCLC) xenografts in vivo (39). However, recent reports showed that the cerebral radionecrotic uptake (40) or stroke (41) resulted in false positive diagnoses of cerebral metastases based on PSMA/CT uptake as limitation of the PSMA-based diagnostic glioma imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation of PSMA expression between metastatic sites and primary tumors has been demonstrated in vivo and in vitro (18,20,21). Early human clinical studies demonstrated activity in breast tissue (22) and breast carcinoma using 111 In-J591 (23) planar imaging, as well as 68 Ga-PSMA-HBED-CC (N,N9-bis[2-hydroxy-5-(carboxyethyl)benzyl]ethylenediamine-N,N9-diacetic acid) PET/CT ( Fig. 1) (20,(23)(24)(25)(26).…”
Section: Breast Cancermentioning
confidence: 97%
“…Lung cancer is the second most common type of cancer in the United States, with over 220,000 new cases a year (14). Although 111 In-J591 (23); 68 Ga-HBED-CC (32,33) Colorectal adenocarcinoma no PSMA expression has been seen in normal lung tissue (2,8,15,16), tumor epithelial cells from various histologic types of lung cancer, as well as neovascular endothelial cells, have demonstrated PSMA expression (8,16,19,30). Furthermore, PSMA expression has been associated with higher histologic grades in non-small cell lung cancer (NSCLC) (31).…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation